Comprehensive Multidisciplinary Management of Postoperative Thoracic Surgery Patients: Imaging Assessment, Intraoperative Support, Respiratory Care, and Early Rehabilitation - Ayed, Alqahtani Saleh; Al Dawsri, Abdullah Saeed Misfer; Alshrudh, Mubark Ali Mubark; Rajhi, Mansour Abdu Abdullah; Alatawi, Tariq Ahmed Sabih; Aldosari, Ali Abdallah Ali; Rajhi, Mohammed Abdu Abdullah; ALGHANNAM, ANAS IBRAHIM; Sayram, Abdullah Ahmed Aqeel; Tumayhi, Bassam Ali; et al. (Saudi Journal of Medicine and Public Health, 2025)
Background: Chest trauma remains a leading cause of morbidity and mortality worldwide, particularly in polytrauma patients. The thorax contains vital organs, and injury can rapidly compromise respiratory and cardiovascular function, making prompt diagnosis and coordinated management essential. Aim: This article aims to provide a comprehensive overview of chest trauma, focusing on anatomy, etiology, pathophysiology, clinical evaluation, imaging modalities, and evidence-based management strategies to improve patient outcomes. Methods: A narrative, multidisciplinary review was conducted, integrating current principles of trauma care, Advanced Trauma Life Support (ATLS) protocols, radiologic assessment, and surgical and non-surgical management approaches for blunt and penetrating thoracic injuries. Results: Chest trauma most commonly results from blunt mechanisms such as motor vehicle collisions and falls, with pneumothorax, hemothorax, pulmonary contusion, and cardiac injury being frequent complications. Early use of chest radiography, eFAST, and computed tomography enhances diagnostic accuracy. Most injuries can be managed nonoperatively with careful monitoring, pain control, respiratory support, and timely intervention when indicated. Surgical management is reserved for specific life‑threatening conditions or refractory cases. Conclusion: Effective chest trauma management requires rapid assessment, accurate imaging, vigilant monitoring, and a multidisciplinary approach. Early recognition and timely intervention significantly reduce preventable morbidity and mortality.